Performance evaluation of graphene oxide–MnO2 nanocomposite for alkaline membrane fuel cell. Issue 3 (6th July 2021) - Ahmed, Mushtaq; Ahmad, Shahbaz; Nawaz, Tahir; Durrani, M. Ali; Ali, Asghar; Saher, Saim; Khan, Muhammad Alam Zaib; Egilmez, Mehmet; Samreen, Ayesha; Mustafa, Faisal
Abstract: The manganese dioxide/graphene oxide (MnO2 /GO) nanocomposites were prepared from hydrothermally synthesized MnO2 nanorods and graphene oxide. Electrocatalytic performance for the oxygen reduction reactions (ORR) of the fabricated MnO2 /GO nanocomposites was evaluated using the rotating disk electrode (RDE) method. It is found that MnO2 /GO nanocomposites deliver significantly enhanced performance compared to standalone MnO2 and GO with current density and onset potential values of 5.1 mA/cm 2 and 0.93 V versus RHE, respectively. The alkaline membrane fuel cell (AMFC) characteristics were also studied. In particular, the single‐cell alkaline fuel cell stack with MnO2 /GO nanocomposite as cathode loading produced a peak power density value of 82 mW/cm 2 . Our findings revealed great potential for MnO2 /GO nanocomposites for their electrocatalytic performance and utilization in AMFC as the cathode. Namely, MnO2 /GO achieved fuel cell functionalities that were comparable to the widely used commercial Pt/C. The enhanced electrochemical performance of MnO2 /GO is attributed to the synergistic interaction between highly conductive GO sheets and active sites of MnO2 nanorods. The commendable performance of MnO2 /GO suggests that it can be used as electrocatalysts in alkaline fuel cell applications.